Breve historia de la Olimpiada peruana de Química (1996-2010) - Chong, Miguel (2010)
The Peruvian Chemistry Olympiad (OPQ) is an annual competition that takes place in Peru since 1996 and consists on a competition among high school students. Around 1500 students from all over the country take part in this event.The winners gain access to international competitions such as the International Chemistry Olympiad (IChO) and the Latin American Chemistry Olympiad (OIAQ).Since 1999 the Peruvian participants have achieved important successes in international competitions. The OPQ is organized mainly by the lecturers, clerks and laboratory technicians from the Chemistry Section of the Pontificia Universidad Católica del Perú.